(untitled) (PerCursos, 2023)
This article aims to reflect on the organizational and mobilizing processes of urban social movements and the effects historically generated on the guidelines of urban reform and its expansion on the Right to the City from the integration with gender, race, indigenous and other issues. For methodological elaboration of the present work we resorted to the specialized bibliography of the urban social movements, of the urban reform and of the right to the city; the documents elaborated in the interlocution processes between the movements and the public power were verified; research and extension reports from PARU and GPPUMA were used as materials that gather systematized information on the processes of mobilization and organization of the “Fronts of the Victims” of the Watershed of Una, Tucunduba and Estrada Nova. Through university extension actions and research carried out, it was possible to verify the dynamics used by the affected fronts, allowing an updated reading of urban social movements in Belém. It appears that the urban struggle of urban social movements and new organizational formats such as the Fronts of the Victims, envision the paths defended by Lefebvre (2021) and Harvey (2014), that the urban revolution is built in the collective struggle of political organization, social and cultural, although limits and correlation of forces are imposed along the way.